THE ROLE OF GENERASI BERENCANA (GENRE) IN GUIDING TEENAGERS TO PREVENT YOUNG MARRIAGE - Latifah Isfuliah; Wahyuningsih Wahyuningsih, Avifah Sauqiyah (CV. ADIBA AISHA AMIRA, 2022)
Generation Planning (GenRe) has an important role in today's era. This is because GenRe is a place to go directly to the community, especially socialization in the field of education or school areas. The forum is PIK-R (Center for Youth Information and Counseling) which has a function to participate in schools in order to provide PKBR (Preparation of Family Planning for Teenagers) so that the realization of Tegar Teens which has the same goal as GenRe, which is to avoid TRIAD KRR (Sexuality, drugs, HIV and AIDS), delaying the age of marriage, and having a family plan to live a prosperous and happy life. The purpose of this study is so that adolescents can reconsider their plans to marry young before the ideal age and provide insight into the impact and preparation for young marriage. The object of this research is Duta GenRe and three people under the age of 20 who are not married. This research method uses qualitative research. The data was obtained by triangulation using primary and secondary data sources to prove the truth of the data. The results of this study are that GenRe has an important role for adolescents, especially as a source of knowledge in the field of marriage that is not obtained at the education level. Thus, knowledge of how to prepare for marriage is needed so that more young marriages do not occur